Gambaran Sikap Penanganan Dismenore pada Remaja Puteri di SMA Swasta St. Petrus Medan Tahun 2024 - Indra Hizkia P; Magda Siringo ringo; Santi Tamara Hutapea (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Menstrual pain problems sometimes become a problem for women when they visit a doctor because of menstruation. This condition becomes worse if accompanied by an unstable psychological state, such as stress, depression, excessive anxiety, and excessive feelings of sadness or happiness. Knowledge about dysmenorrhea has a significant impact on attitudes towards dysmenorrhea, women who have sufficient knowledge and get the right explanation about dysmenorrhea about dealing with symptoms and complaints with an enthusiastic attitude. This study aims to determine the Picture of Dysmenorrhea Handling Attitudes in Adolescent Girls at SMA St. Petrus Medan in 2024. This study uses a quantitative method with a descriptive research type. This study uses a questionnaire with a research population of 107 respondents. Sampling was carried out using a purposive sampling technique with a total of 53 respondents. The results of the study showed that Adolescent Girls at SMA St. Petrus Medan 2024 regarding attitudes towards signs and symptoms of dysmenorrhea as many as 44 respondents (83.0%) in the negative category, attitudes towards preventing dysmenorrhea as many as 27 respondents (50.9%) in the negative category, attitudes towards handling dysmenorrhea as many as 33 respondents (62.3%) in the negative category, attitudes towards handling 44 respondents (83.0%) in the negative category. It is hoped that there will be an increase in health education about handling dysmenorrhea carried out by health workers and teachers to improve the knowledge of female students of St. Petrus High School regarding handling dysmenorrhea.